Development of a mechanical model of doctor blade–press roll tribosystem with aim to optimise cleaning performance: numerical predictions and first experimental verification. (March 2014) - Rodríguez Ripoll, M.; Scheichl, B.; Bianchi, D.; Jakab, B.; Franek, F.
<x content-type="archive" xml:space="preserve">Abstract</x> In the paper production, doctor (scraping) blades are placed in contact with press rolls during wet pressing so as to purge the surface of the rolls from processing water, contamination and stickies. The contact is achieved by mounting the blade on a holder, which is tilted around a rotation axis until the blade tip contacts with the roll. The contact force is determined by the supply pressure of the air forced through the tube that is placed at the bottom of the holder. Owing to contact, the blade wears off and needs to be replaced periodically. Our aim is to optimise the cleaning performance of the system by modelling the tribological contact between the doctor blade and press roll in order to achieve an optimum cleaning performance, thus increasing the blade lifetime and reducing energy consumption. The model is susceptible to an inextensive numerical evaluation as compared to that of a more advanced modelling approach, e.g. in terms of a full finite element analysis of the beam deflection. A first comparison with experimental findings is encouraging.